Cost-utility analysis of repetitive transcranial magnetic stimulation as add-on therapy to standard care for the treatment of hallucinations in schizophrenia. Issue 1 (30th March 2022) - Hendriks, Lauren; Mihalopoulos, Cathrine; Le, Long Khanh-Dao; Loo, Colleen; Chatterton, Mary Lou
Abstract: Background: This research evaluates the cost-effectiveness of repetitive transcranial magnetic stimulation (rTMS) as add-on therapy to standard care for adults with schizophrenia from an Australian health system perspective. Methods: A Markov model estimated costs in 2021 Australian dollars and Disability-Adjusted Life-Years (DALYs) averted with rTMS added to standard care compared to standard care alone over 12-months for adults aged 25–65 years with hallucinations in schizophrenia refractory to other therapies. rTMS effect size was sourced from a meta-analysis and converted to a relative risk using the Cochrane conversion method. Probabilistic sensitivity analysis evaluated uncertainty in effect size and disability weights. One-way sensitivity analyses varied rTMS session cost and effectiveness, time horizon and inpatient costs. Results: The base-case average incremental cost-effectiveness ratio (ICER) was 87, 310/DALY averted (95% UI: 10, 157–97, 877). Reducing rTMS session cost to 100 lowered the ICER to 9, 127/DALY (95% UI: Dominant–50, 699). A 4-year time horizon resulted in rTMS being less costly and more effective (Dominant) than standard care. Decreasing the 3-month probability of relapse with rTMS to 4.6% resulted in a 71% probability of rTMS being cost-effective. Conclusions: Using a threshold of 50, 000/ DALY averted, rTMS as add-on therapy to standard care for the treatment of refractory hallucinations in schizophrenia would not be considered a cost-effective treatment option compared to standard care alone. However, given the refractory nature of this condition and the relatively small size of this population, it may be reasonable for decision-makers to adopt a higher ICER threshold.